Nonunion Worker Representation, Foreign Owners and the Performance of Establishments - Uwe Jirjahn; Steffen Mueller (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
Using German establishment data, this study provides the first econometric analysis on the interaction of establishment-level codetermination and foreign owners. Works councils are associated with higher productivity in domestic-owned establishments while they are associated with lower productivity in foreign-owned establishments. Moreover, the estimates show that the interaction of works councils with the broader industrial relations system also depends on the type of ownership. Works council incidence and collective bargaining coverage have a positive interaction effect on productivity in domestic-owned establishments. No such interaction effect can be found in foreign-owned establishments.
Keywords: J53; J54; M54; 330; Works Council; Foreign Owners; Collective Bargaining; Productivity